Hagopian, David G., ed., Kembali ke Dasar-dasar: Menemukan Kembali Kekayaan Iman Reformed, terj. Arvin Saputra. Surabaya: Momentum, 2018: xviii + 321 halaman, ISBN: 602-393-059-X - Prasetyo, Nurcahyo Teguh (Theologia in Loco, 2020)
book review